Rethinking Islamic Feminist Thought on Reinterpreting the Qur'an: An Analysis of the Thoughts of Aminah Wadud, Fatima Mernissi, Asma Barlas, and Riffat Hassan - Dwi Fidhayanti; Muhammad Muhammad; Mahbub Aunur Rofiq; Muhammad Robith Fuadi; Abdul Hakim; Nabrisatul Chusna Bil Makkiy (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
This article aims to revisit Islamic feminist thought on the reinterpretation of the Qur'an by analyzing the views of four major figures in the movement: Aminah Wadud, Fatima Mernissi, Asma Barlas, and Riffat Hassan. This study uses a critical text analysis approach to understand the arguments and interpretations they put forward in interpreting Qur'anic verses related to gender. Through an in-depth analysis of their work in articles, books, and papers of their views. In addition, the article explores the ways in which these Islamic feminists reconstruct an understanding of sacred texts, highlighting differences in approach and common themes in their interpretations. In addition, it evaluates the impact of their reinterpretations of the Qur'an on traditional views in Muslim societies and their implications in the context of social change and gender equality. When examining Islamic feminist views on the Qur'anic reinterpretation, it is important to thoroughly understand the cultural and linguistic context of Arabic. Misconceptions regarding the interpretations of classical Muslim intellectuals, which are often considered discriminatory against women, are often due to a lack of understanding of the cultural and linguistic context of Arabic. Therefore, it is important to pay attention to linguistic and cultural contexts when interpreting sacred texts. On the other hand, feminists should also note that interpretations of the Qur'an do not always result in interpretations that are in line with their principles of gender equality. The theoretical implication is that, in an effort to understand the verses of the Qur'an related to gender issues, it is important to consider the cultural context, language, and comprehensive interpretation. There is room for dialog and deeper understanding between feminist views and traditional interpretations, by taking an approach that combines an understanding of classical Arabic culture with the values of gender equality championed by feminists.